Fieber’s original drawings and their corresponding types for the family Issidae (Hemiptera, Fulgoromorpha) in the Muséum national d’Histoire naturelle of Paris, France - Gnezdilov, Vladimir M.; Soulier-Perkins, Adeline; Bourgoin, Thierry (Zootaxa, 2011)
Lectotypes are designated for 10 species described by Fieber, deposited in MNHN, Paris: Issus climacus Fieber, 1876, I. frontalis Fieber, 1876, I. truncatus Fieber, 1876, I. fissala Fieber, 1876, Hysteropterum angulare Fieber, 1877, H. melanophleps Fieber, 1877, H. fuscovenosum Fieber, 1877, H. striolatum Fieber, 1877, H. impressum Fieber, 1877, Mycterodus sulcatus Fieber, 1876. Iberanum nuragicum Gnezdilov & Mazzoni, 2003 is placed in synonymy under Hysteropterum fuscovenosum Fieber, 1877 and Issus novaki Dlabola 1959 under Issus frontalis Fieber, 1876. A new genus Thabenula is erected for Mycterodus sulcatus Fieber, 1876. Six new generic combinations are proposed: Hysteropterum melanophleps Fieber, 1877 is transferred to the genus Tingissus Gnezdilov, 2003, Hysteropterum fuscovenosum Fieber, 1877 to the genus Iberanum Gnezdilov, 2003, Hysteropterum phaeophleps Fieber, 1877 to the genus Palmallorcus Gnezdilov, 2003, Hysteropterum striolatum Fieber, 1877 to the genus Tshurtshurnella Kusnezov, 1927 and Issus fissala Fieber, 1876 to the genus Thabena Stål, 1866. Fourteen species described by Fieber are illustrated with his original drawings.